The APOA1 p.Leu202Arg variant potentially causes autosomal recessive cardiac amyloidosis - Shusuke Yagi; Ryosuke Miyamoto; Masayoshi Tasaki; Hiroyuki Morino; Ryuji Otani; Muneyuki Kadota; Takayuki Ise; Hiroki Yamazaki; Kenya Kusunose; Koji Yamaguchi; Hirotsugu Yamada; Takeshi Soeki; et al. (Human Genome Variation)
Abstract ApoA-I amyloidosis is an extremely rare form of systemic amyloidosis that commonly involves the heart, kidneys, and liver. ApoA-I amyloidosis is caused by amyloidogenic variants of APOA1 that are inherited in an autosomal dominant manner. Here, we report a 69-year-old man with sporadic cardiac amyloidosis who was born to consanguineous parents and carried a homozygous variant of p.Leu202Arg in APOA1.